Analysis of Ecological Environment Problems and Countermeasures in Ideological and Political Education in Colleges and Universities. (12th October 2022) - Hao, He
Abstract : At present, there are many problems in the mode and method of ideological and emotional education of college students. The state attaches great importance to this aspect and continues to increase investment, but the effect is not satisfactory. As an important field for cultivating high-level socialist talents, colleges and universities have played a huge role in promoting the ideological development and emotional education of college students. The emergence of this contradiction shows that traditional educational methods have their own shortcomings and need to expand their thinking and explore new research areas. Since the new era, the ideological education venues and teaching activities of colleges and universities have been greatly improved, but they are also facing many problems and challenges, which seriously affect the moral quality of college students and destroy the ideological education ecosystem of colleges and universities. From the perspective of the ecological crisis of education, this paper awakens and pays attention to the ecological problems of education, making it an inevitable trend of current education development and paving the way for future research. On this basis, the current situation of the ecology of political education of college students is analyzed, and the necessity of research is proposed. Analyzing the ideological and emotional education of college students from the perspective of ecology is essentially to regard the ideological education of college students as an ecosystem and deeply analyze the distribution of various components and elements of college students' ideological and political education. The ecology of college students' ideological education is the process, law, and overall ecological balance of various factors in the ideological education system of college students, as well as the methodological thinking and value orientation of the interaction between various factors and the environment. The changes of the ecological environment have a significant impact on people's state of mind. As college students growing up in the new environment, their thoughts, emotions, and values are all affected by the development of the ecological environment. Therefore, changes in the ecological environment, air quality, and water environment have increasingly obvious impacts on the living environment.